The Role of Experience and Ability in Comprehension Tasks Supported by UML Stereotypes - Ricca, F.; Di Penta, M.; Torchiano, M.; Tonella, P.; Ceccato, M. (29th International Conference on Software Engineering (ICSE'07), 2007)
Proponents of design notations tailored for specific application domains or reference architectures, often available in the form of UML stereotypes, motivate them by improved understandability and modifiability. However, empirical studies that tested such claims report contradictory results, where the most intuitive notations are not always the best performing ones. This indicates the possible existence of relevant influencing factors, other than the design notation itself. In this work we report the results of a family of three experiments performed at different locations and with different subjects, in which we assessed the effectiveness of UML stereotypes for Web design in support to comprehension tasks. Replications with different subjects allowed us to investigate whether subjects' ability and experience play any role in the comprehension of stereotyped diagrams. We observed different behaviors of users with different degrees of ability and experience, which suggests alternative comprehension strategies of (and tool support for) different categories of users.